Effect of drying method and storage conditions on the essential oil yield and composition in Eugenia uniflora L. leaves - Assis, Ana Lucia Alves de; Cipriano, Roger Raupp; Cuquel, Francine Lorena; Deschamps, Cícero (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2020)
The essential oil produced by Eugenia uniflora leaves is intensively used by the cosmetic, pharmaceutic and perfumery industries mainly because its antioxidant effect and antimicrobial and antihelmintic ativities. Drying and storage of the aromatic plant leaves can affect the yield and quality of its essential oil. This study aimed to evaluate the effect of drying method and storage conditions on the essential oil yield and composition in Eugenia uniflora leaves. The essential oil were extracted from dried leaves at ambient temperature and at 45°C for six drying periods (0, 6, 24, 48, 72 and 96 hours-h). The essential oil yield was also analysed after 0, 60, 120, and 180 days of storage in three types of packaging. The oil was extracted by hydrodistillation and the composition was determined by gas chromatography-mass spectrometry. Results showed that drying the leaves at ambient temperature and 45°C for 48 and 24 h, respectively, increased the essential oil yield. At 45°C the monoterpene and sesquiterpene compounds increased, with curzerene+viridiflorene identified as the major compounds. Package types did not affect the essential oil yield but the increase of the storage period decreased it.